2008
DOI: 10.1021/bi702416b
|View full text |Cite
|
Sign up to set email alerts
|

Solution X-ray Scattering Reveals a Novel Structure of Calmodulin Complexed with a Binding Domain Peptide from the HIV-1 Matrix Protein p17

Abstract: The solution structures of complexes between calcium-saturated calmodulin (Ca (2+)/CaM) and a CaM-binding domain of the HIV-1 matrix protein p17 have been determined by small-angle X-ray scattering with use of synchrotron radiation as an intense and stable X-ray source. We used three synthetic peptides of residues 11-28, 26-47, and 11-47 of p17 to demonstrate the diversity of CaM-binding conformation. Ca (2+)/CaM complexed with residues 11-28 of p17 adopts a dumbbell-like structure at a molar ratio of 1:2, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Although a similar number of chemical shift perturbations were expected from residues in the C-terminal lobe, relatively few were actually observed to change upon MA binding, comprising only two (L105 and T110) out of thirteen chemical shifts unambiguously assigned to residues in that lobe. The lack of perturbed chemical shifts in the C-terminal lobe may be due to the relative scarcity of assignments on our NMR experiment for residues in this region that have previously been identified to form contacts with target molecules (F92, V108, M109, F141, M144, and M14524; 41). It is also possible that the CaM-MA interaction is principally mediated by the N-terminal lobe, and we note that the proposed model by Izumi and colleagues also shows a disproportionate number of MA contacts from that lobe.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although a similar number of chemical shift perturbations were expected from residues in the C-terminal lobe, relatively few were actually observed to change upon MA binding, comprising only two (L105 and T110) out of thirteen chemical shifts unambiguously assigned to residues in that lobe. The lack of perturbed chemical shifts in the C-terminal lobe may be due to the relative scarcity of assignments on our NMR experiment for residues in this region that have previously been identified to form contacts with target molecules (F92, V108, M109, F141, M144, and M14524; 41). It is also possible that the CaM-MA interaction is principally mediated by the N-terminal lobe, and we note that the proposed model by Izumi and colleagues also shows a disproportionate number of MA contacts from that lobe.…”
Section: Resultsmentioning
confidence: 97%
“…Izumi and colleagues41 have previously generated a model for the Ca 2+ -CaM-MA interaction using MA peptides corresponding to residues 11–47 and proposed that a group of charged residues in CaM on the N-terminal lobe and within the central helix form direct electrostatic contacts with MA. They proposed a novel interaction that excluded the involvement of CaM’s hydrophobic clefts that are typically responsible for CaM-target binding, and rather suggested that CaM could interact with MA without the involvement of the large hydrophobic residues internal to the MA core that would require a conformational change in the MA structure.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and in vitro studies revealed that CaM interacts with additional HIV-1 proteins like Nef, Tat, and gp160 (27,34,37,52,53,56). Small-angle x-ray scattering studies have provided a global picture of CaM bound to full-length MA (57) or to short peptides derived from the MA protein (58). Our laboratory (59) and others (57,60) have shown that CaM binds directly to the MA protein in a calcium-dependent manner.…”
mentioning
confidence: 96%
“…These studies have prompted others to conduct SAXS experiments to elucidate the global features of CaM bound to short peptides derived from the MA protein (Izumi et al, 2008). SAXS studies conducted on CaM complexed with full-length MA shed light on the global features of the complex (Chow et al, 2010).…”
Section: Potential Role Of Cam In Hiv Replicationmentioning
confidence: 99%